2018
DOI: 10.1007/s00706-018-2206-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unsymmetrical disulfanes bearing 1,2,4-triazine scaffold and their in vitro screening towards anti-breast cancer activity

Abstract: A new series of 1,2,4-triazine unsymmetrical disulfanes were prepared and evaluated as anticancer activity compounds against MCF-7 human breast cancer cells with some of them acting as low micromolar inhibitors. Evaluation of the cytotoxicity using an MTT assay, the inhibition of [3H]-thymidine incorporation into DNA demonstrated that these products exhibit cytotoxic effects on breast cancer cells in vitro. The most effective compounds with 59 and 60 µM compared to chlorambucil with 47 µM were disulfanes beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Recently, the novel 1,2,4-triazole derivatives have been implicated in mediating antitumor activities. These compounds have inhibitory effects on the growth of several types of cultured cancer cells, including leukemia, and breast and colorectal cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the novel 1,2,4-triazole derivatives have been implicated in mediating antitumor activities. These compounds have inhibitory effects on the growth of several types of cultured cancer cells, including leukemia, and breast and colorectal cancer [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Bielawski and coworkers have performed an oxidative cross‐coupling between disulfides and thiols for the synthesis of 1,2,4‐triazine unsymmetrical disulfide ( Scheme 32). [11] The K 2 CO 3 was initially applied as a reagent in this approach, however, the yield of unsymmetrical disulfides was not satisfying (19–43 %). Then, 2,3‐dichloro‐5,6‐dicyanobenzoquinone (DDQ) was used as a commercially available oxidant for the reaction between aryl disulfides with thiols such as aryl, alkyl, and heteroaryl thiols which furnished the corresponding unsymmetrical disulfides in moderate yields.…”
Section: Synthesis Of Unsymmetrical Organic Disulfidesmentioning
confidence: 99%
“…The formation of the S−S bond has been employed for facilitating protein refolding, the prodrug synthesis, increase the hydrophobicity or cell permeability [8–10] . The 1,2,4‐triazine unsymmetrical disulfides displayed the anticancer activity against MCF‐7 human breast cancer cells [11] . The complexes between thiols, disulfides, and trisulfides with ruthenium porphyrins have been studied as a model for Fe−S bonds in heme proteins [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Perusal of the literature reveals a variety of methods for synthesizing disulfides and a great number of disulfide analogues had been designed and synthesized. For example, Xu Qiu et al [ 8 ] demonstrated a novel carbonate salts catalyzed aerobic oxidative heterocoupling of thiols for the efficient synthesis of unsymmetrical disulfides; D. Branowska et al [ 9 ] had described a series of new 1,2,4-triazine unsymmetrical disulfane analogues that were prepared and evaluated as anticancer activity compounds against MCF-7 human breast cancer cells with some of them acting as low micromolar; J. K. Vandavasi et al [ 10 ] have developed an efficient ‘one pot’ method for the synthesis of unsymmetrical dithio compounds directly from corresponding thiols and thiocarboxylic acids in the presence of DDQ (2,3-Dichloro-5,6-dicyano-1,4-benzoquinone). In addition, F. Yang et al [ 11 ] have also developed one-pot synthesis of aromatic-aromatic and aromatic-aliphatic disulfide unsymmetrical disulfide using TCCA (Trichloroisocyanuric Acid).…”
Section: Introductionmentioning
confidence: 99%
“…Disulfides exist in many synthetic and natural products and have been applied extensively in organic transformation and medicinal chemistry. As example, ajoene and dysoxysulfone are found in garlic, onions and mahogany trees and have shown promising antifungal [ [15] , [16] ], antibacterial [ 17 ], antitumor [ 9 , 18 ], antimalarial [ 19 ] and analgesic properties [ 20 ].…”
Section: Introductionmentioning
confidence: 99%